Reevaluating the relationship between female sociality and infant survival in wild baboons - Maria J. A. Creighton; Brian A. Lerch; Elizabeth C. Lange; Joan B. Silk; Jenny Tung; Elizabeth A. Archie; Susan C. Alberts (Proceedings of the National Academy of Sciences, 2025)
Over the past few decades, studies have provided strong evidence that the robust links between the social environment, health, and survival found in humans also extend to nonhuman social animals. A number of these studies emphasize the early life origins of these effects. For example, in several social mammals, more socially engaged mothers have infants with higher rates of survival compared to less socially engaged mothers, suggesting that positive maternal social relationships causally improve offspring survival. Here, we show that the relationship between infant survival and maternal sociality is confounded by previously underappreciated variation in female social behavior linked to changes in reproductive state and the presence of a live infant. Using data from a population of wild baboons living in the Amboseli basin of Kenya—a population where high levels of maternal sociality have previously been linked to improved infant survival—we find that infant- and reproductive state-dependent changes in female social behavior drive a statistically significant relationship between maternal sociality and infant survival. After accounting for these state-dependent changes in social behavior, maternal sociality is no longer positively associated with infant survival in this population. Our results emphasize the importance of considering multiple explanatory pathways—including third-variable effects—when studying the social determinants of health in wild populations.